QR TECHNOLOGY - CODING AND ITS IMPLEMENTATION IN THE EDUCATIONAL PROCESS OF HIGHER SCHOOL - Niedialkova Катерина (Journal of Information Technologies in Education (ITE), 2020)
The presented article reveals the essence of QR-coding technology and the possibility of its use in the educational process, in particular higher education. QR-codes allow you to get instant access to any information from the Internet using smartphones. With the involvement of QR-codes it is possible to diversify the educational process and increase the interest of both pupils and students to study the subject. At the same time, the use of QR-codes is associated with a number of problems that should be considered when implementing this technology in the educational process.Regarding higher education, researchers have found that two-dimensional barcodes can be used at different stages of learning: explanation, generalization, systematization or verification of the studied material, when assessing student achievement, etc., and during such work can combine traditional and interactive forms of organization educational activities.The purpose of the pedagogical experiment by the author of this article was to determine the effectiveness of the systematic application of QR-technology in the process of professional training of future teachers of mathematics in the context of the competence approach. During the teaching of the discipline "School course of mathematics and methods of its teaching" during the semester in experimental groups during lectures and practical classes offered QR-links to electronic textbooks, reference information, presentations, interesting facts, training simulators, training tests, scientific articles, methodical developments, lesson outlines, etc. In addition, the author has developed a QR-dictionary of concepts of general methods of teaching mathematics, and each student –QR-dictionary of concepts on a particular topic of the course of methods of teaching algebra; together, future teachers prepared and conducted a QR-quest for pupils in order to increase interest in learning mathematics.The result of this work was to increase the success and interest of students in experimental groups in the study of the professional discipline, compared with the success of students in control groups, and more effective formation of some professional competencies.